DECODING THE PAST: THE DETECTIVE GENRE’S JOURNEY THROUGH HISTORY - Амонова Дилшода Азамат кызы (Western European Studies, 2025)
This article provides an in-depth scientific and theoretical analysis of the formation and evolution of the detective genre. Originating in the 19th century through the pioneering works of Edgar Allan Poe, this literary form has undergone significant stylistic and thematic transformations over time, solidifying its place within world literature. The study explores the social and psychological aspects of detective fiction while examining contemporary trends in the genre. By drawing upon scholarly sources and literary criticism, this research evaluates the dynamics of change in detective fiction, tracing its evolution from its earliest manifestations to its modern-day developments
Keywords: detective genre; classic detective; hard-boiled detective